ORF6 from the clavulanic acid gene cluster of Streptomyces clavuligerus has ornithine acetyltransferase activity. - Kershaw, N; McNaughton, H; Hewitson, K; Hernández, H; Griffin, J; Hughes, C; Greaves, P; Barton, B; Robinson, C; Schofield, C (2002)
The clinically used beta-lactamase inhibitor clavulanic acid is produced by fermentation of Streptomyces clavuligerus. The orf6 gene of the clavulanic acid biosynthetic gene cluster in S. clavuligerus encodes a protein that shows sequence homology to ornithine acetyltransferase (OAT), the fifth enzyme of the arginine biosynthetic pathway. Orf6 was overexpressed in Escherichia coli (at approximately 15% of total soluble protein by SDS/PAGE analysis) indicating it was not toxic to the host cells. The recombinant protein was purified (to > 95% purity) by a one-step technique. Like other OATs it was synthesized as a precursor protein which underwent autocatalytic internal cleavage in E. coli to generate alpha and beta subunits. Cleavage was shown to occur between the alanine and threonine residues in a KGXGMXXPX--(M/L)AT (M/L)L motif conserved within all identified OAT sequences. Gel filtration and native electrophoresis analyses implied that the ORF6 protein was an alpha2beta2 heterotetramer and direct evidence for this came from mass spectrometric analyses. Although anomalous migration of the beta subunit was observed by standard SDS/PAGE analysis, which indicated the presence of two bands (as previously observed for other OATs), mass spectrometric analyses did not reveal any evidence for post-translational modification of the beta subunit. Extended denaturation with SDS before PAGE resulted in observation of a single major beta subunit band. Purified ORF6 was able to catalyse the reversible transfer of an acetyl group from N-acetylornithine to glutamate, but not the formation of N-acetylglutamate from glutamate and acetyl-coenzyme A, nor (detectably) the hydrolysis of N-acetylornithine. Mass spectrometry also revealed the reaction proceeds via acetylation of the beta subunit.